Velo-cine, uma fábrica de projetores no nordeste brasileiro: uma abordagem arqueológica da mídia cinema - Dib, André Huchi (2022)
Between 1959 and 1983, a factory based in Pernambuco produced more than a hundred projectors, equipping and providing maintenance services for movie theaters in capitals and in the interior of Brazil’s northeast. By offering such products and services, Indústria Velo-Cine Ltda. established itself as the main alternative given the high cost of acquisition and maintenance of projectors made in the southeast region. By using media archeology approaches (ELSSAESSER, 2018; ZIELINSKI, 2006; and KITTLER, 2016) and parameters related to projector display and manufacturing techniques in Brazil (LUCA, 2012; FREIRE, 2013 and 2018), and from family members, exhibitors, projectionists and cinema technicians testimonials; the analysis of equipment produced by the factory; and the mapping of cinemas that used its products and services, this research investigates factors and conditions that allowed the existence of the Velo-Cine brand. As a result, it presents unpublished information that allows to know and put into context this, which is possibly the only brazilian company to assembly, manufacture and sale film projection equipment in 35mm operating outside the southeast. In the quest to understand the relationship between the specific demands of the regional exhibition circuit and how they were answered by Velo-Cine, this dissertation relates to issues such as the movie theater as a media device and the appropriation of technologies and hegemonic content in peripherals environments.